1983
DOI: 10.1071/ch9830545
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of methyl-substituted Hex-5-enyl and Pent-4-enyl radicals

Abstract: Relative and absolute kinetic data have been determined for ring closure of methyl-substituted hex-5-enyl radicals: 2-methyl- (10a), 3-methyl-(4a), 4-methyl-(5a), 2,2-dimethyl-(10c), 3,3-dimethyl-(4c) and 4,4-dimethyl-hex-5-enyl (5c) radicals, generated by interaction of tributylstannane with the corresponding bromides (1a)-(3a) and (1c)-(3c). Each radical undergoes regiospecific or highly regioselective 1,5-cyclization more rapidly than does the unsubstituted radical (4d). The rate enhancements, which arise m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(98 citation statements)
references
References 0 publications
7
91
0
Order By: Relevance
“…This can be explained by a Beckwith-type model (Scheme 35). [50] From mechanistic considerations, the reactivity is quite similar to that for the hydroetherification reported above (Scheme 29). Indeed, the alkene is first oxidized by the photoexcited catalyst.…”
Section: Multiple-bond-centered Radical-mediated Reactivitysupporting
confidence: 57%
“…This can be explained by a Beckwith-type model (Scheme 35). [50] From mechanistic considerations, the reactivity is quite similar to that for the hydroetherification reported above (Scheme 29). Indeed, the alkene is first oxidized by the photoexcited catalyst.…”
Section: Multiple-bond-centered Radical-mediated Reactivitysupporting
confidence: 57%
“…It leads preferentially to 1,5-cis-disubstituted cyclopentanes, according to the Beckwith transition state model. [3] This model postulates an early transition state, which resembles a "chair-like" cyclohexane ring with substituents in pseudo-equatorial rather than pseudo-axial [4] positions. In the second case Equation (2), we have a stereogenic center at C-2.…”
Section: Introductionmentioning
confidence: 99%
“…The cyclization of the parent pent-4-enyl radical, also complicated by reversibility, has never been observed, and Athel had to resort to an estimate of the maximum possible rate at which it could have cyclized without products being detectable under the conditions used at the time. [3,[21][22][23] The essentially complete exo-selectivity of this unobserved cyclization would be expected to be similar to its immediate homologues on stereoelectronic grounds.…”
Section: Regioselectivity Explainedmentioning
confidence: 99%
“…[29] Cyclizations of hex-5-enyl radical bearing simple alkyl or alkenyl substituents at the non-reacting C-2 15, C-3 16, and C-4 17 positions (Scheme 7) also proceed at enhanced rates compared with the parent unsubstituted radical 1. [22,[31][32][33] Ph.D. student Tony Lawrence conducted a systematic study of the effect of methyl substituents at all three positions and found modest rate enhancements (1.9-3.5) for single methyl groups and more substantial ones (10.8-16.3) for geminal dimethyl groups. Other singly substituted (vinyl, allyl, propyl) hexenyl radicals had roughly comparable relative cyclization rates to those with single methyl groups at the same position.…”
Section: Substituent Effectsmentioning
confidence: 99%
See 1 more Smart Citation